A Comparison between Acetaminophen Suppository and Caudal Anesthesia in Relieving Pain after Pediatric Surgery - Razavi, S S; Shaeghi, S; Shiva, H; Momenzadeh, S (Urology Journal, 2009)
Purpose: Our aim was to provide a simple, non-invasive, low cost, and practical method to be used by nurses and technicians in a low hazardous, safe, and painlessness anesthesia. Materials and Methods: In a prospective blind clinical trial 40 children between 4 and 6 months who were candidated for subumbilical elective surgeries were recruited. They were randomly divided into two groups. Bupivacain 0.25% was prescribed in the control group according to Armitage formula (0.5- 1 ml/kg); while, supp. Acetaminophen was administered in the subject group by a dosage of 30-40 mg/kg. Results: There was no statistically significant difference in the pain score of the two groups within 2 hours postoperatively, but higher pain score was reported in subject group during the third and forth hours. Conclusion: Caudal anesthesia with bupivacaine has better painless period postoperatively.